Analysis of volatile flavor components of sauce-flavor Baijiu of different aging years - LAI Yucheng, GUO Hongli, ZHANG Jiaojiao, XIAN Tingting, SUN Zhiwei, LI Jin, LIU Haipo, ZHAO Jinsong, HAN Xinglin (Zhongguo niangzao)
Using the sauce-flavor (Jiangxiangxing) Baijiu samples (Y5-Y17) aged for 5 to 17 years as the research object, the volatile flavor components and organic acid contents were detected using gas chromatography-flame ionization detector (GC-FID) and ion chromatography (IC). The characteristic differential volatile flavor components of Baijiu samples in different aging years were screened using partial least squares-discriminant analysis (PLS-DA). The results showed that 51 kinds of volatile flavor components were detected, including 13 alcohols, 6 acids, 18 esters, 7 aldehydes and ketones, 4 aromatics and 3 others. The volatile flavor components in 13 samples of sauce-flavor Baijiu were mainly esters (2 863.85-5 366.10 mg/L), alcohols (1 279.77-4 695.78 mg/L) and acids (2 191.60-3 053.50 mg/L). Among them, the contents of esters, alcohols and acids were the highest in Y5 sample, and the total contents of other components were the highest in Y6 sample. After that, as the storage year increased, the contents showed a downward trend, while the total contents of aldehydes and ketones and aromatic components had no change significantly with the storage year increase. PLS-DA result showed that the sauce-flavor Baijiu aged for less than 10 years and more than 10 years could be distinguished. Based on the variable importance projection (VIP) value, 13 characteristic differential volatile flavor components (VIP value>1), including para-butanol, ethyl lactate and isoamyl caproate, were screened. Among them, para-butanol and ethyl lactate were important characteristic differential volatile flavor components.